Intestinal Morphology, Protein Digestibility, and Broiler Performance Fed Encapsulated Dahlia Tuber Extract and Bacillus subtilis - Anjani, L.; Yunianto, V. D.; Suthama, N.; Krismiyanto, L. (Faculty of Animal Science, IPB University, 2025)
This study aimed to evaluate the effects of encapsulated dahlia tuber extract and Bacillus subtilis (EdteBs) on intestinal morphology, protein digestibility, and broiler performance. A total of 200 eight-day-old Ross 308 broilers (initial body weight: 194.60 ± 3.46 g) were divided into four dietary treatments with five replications. The treatments were: T0 – basal diet (control) without EdteBs supplementation; T1 – T0 + 0.1% EdteBs; T2 – T0 + 0.2% EdteBs; and T3 – T0 + 0.3% EdteBs. Variables measured included potential hydrogen (pH), lactic acid bacteria (LAB) population, coliform count, villus height, crypt depth, intestinal segment weight and height, protein digestibility, feed intake, body weight gain (BWG), feed conversion ratio (FCR), and income over feed cost (IOFC). Data were analyzed using analysis of variance, followed by Duncan’s test at a 5% significance level (p<0.05). Results showed that EdteBs supplementation at higher levels (T2 and T3) significantly (p<0.05) increased LAB population, villus height, crypt depth, and intestinal segment weight and height, while pH and coliform counts decreased. Protein digestibility and BWG also significantly improved (p<0.05) in T2 and T3. Both feed intake and BWG increased, particularly in T3, contributing to lower FCR and higher IOFC. In conclusion, EdteBs supplementation enhances intestinal morphology, protein digestibility, and broiler performance, with the most effective level at 0.3%.